Praxiologias docentes na perspectiva intercultural crítica e os desafios de uma educação linguística decolonial - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The main goal of this study was to propose a critical reflection by problematizing experiences and praxiologies of English teachers who work at the public state education of Goiás, more precisely in regards to the possibilities and challenges to promote a linguistic education under a critical intercultural perspective (CANDAU, 2020; DAMÁZIO, 2008; KUBOTA, 2004; MOREIRA, FURLAN, 2022; OLIVEIRA, SABOTA, 2020; RODRIGUES, SILVESTRE, 2020; WALSH, 2009, 2012, 2023) and decolonial ways of thinking (BORELLI, 2018; BORELLI, PESSOA, 2019; MIGNOLO, 2011, 2017; MIGNOLO, WALSH, 2018, PENNYCOOK et al., 2023, REZENDE, 2022, SEGATO, 2021) in such context. Three teachers from the state education of Goiás – Malu, Aurora and Clarice – shared their experiences and praxiologies through speaking reports and written and/or visual contents, in four online meetings of a focus group. Before the encounters began, the teachers answered an initial questionnaire about their contact with the intercultural and decolonial perspectives of linguistic education. Among the (un)continuing thoughts that this study elicits, it is noticeable the fact that, in many cases, the teachers’ talks and praxiologies tended towards a multiculturalist conception (KUBOTA, 2004) that, based on a harmonic intercultural view of the world, sets ground for a functional articulation of interculturality (WALSH, 2009). The teachers’ sharings showed varied counter-hegemonic efforts, arranged with the thoughtfulness of approaching their classes to their students’ realities and, at the same time, devoid of more problematizing attitudes in the construction of pathways towards decoloniality.
Teaching praxiologies in a critical intercultural perspective and the challenges for a decolonial language education
Keywords: Educação linguística crítica; Educação pública - Praxiologias; Interculturalidade crítica; Educação pública - Decolonialidade; CIENCIAS HUMANAS::EDUCACAO